Formuły salutacyjne w korespondencji z terenu Kresów Południowo-Wschodnich (XVII-XVIII w.) = Salutations in letters from the South-Eastern Borderland (17th-18th centuries) - Sicińska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper describes salutations in the 17th- and 18th-century epistolography. As one of the components of the initial part of a letter, salutation is an equivalent of a greeting in a live conversation. This formulaic expression is a more or less extended vocative form of address.
Keywords: historia języka polskiego; epistolografia; etykieta językowa; salutacja; Kresy Południowo-Wschodnie; history of the Polish language; epistolography; verbal etiquette; salutation; South-Eastern Borderland